POLITICAL IMAGE OF THE WORLD IN THE ELECTION POSTER IN SERBIA FROM 1990 TO 2017 - Atlagić, Siniša (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2018)
The aim of this paper is to identify the elements of the political image of the world that the electoral actors in Serbia have been trying to develop through mass political communication from the re-establishment of the multiparty system to the present day. The author of the paper decided to accomplish the given goal by examining the application of basic psychological mechanisms of forming and maintaining the image of the world in creation of electoral posters. The research was approached from the point of social psychology using a constructivist approach. The basic method used in the research is a qualitative content analysis. The selection of posters was preceded by the determination of the so-called situation context factors – the socio-political circumstances in which the posters were created, which is related to the character of the basic method of research. Election campaigns, understood as the final stage in the long-term strategy of the propaganda performances of political actors, were taken as the basic contextual framework for the interpretationof what the communicator sought to say through the posters. The analysis of the posters used in the election campaigns run in 1997, 2000 and 2016 was carried out. The results of the analysis showed that, regarding the application of psychological mechanisms in creation of the "image of the world," the election poster in Serbia is complex. The conclusion is that the political "image of the world" of voters in Serbia created during the 1990s is similar to their current view of the political environment and that its basic characteristics are the identification with the state and a pronounced stereotype of a strong leader.